(untitled) (American Journal of Islam and Society, 2013)
The notion that Islam is “Becoming an American Religion” may be unnerving to those who see America’s roots in its Christian, and more recently Judeo-Christian, heritage. Yet, given the rate of growth and development of American Muslim institutions and social networks, it may be more apt to speak of Islam as part of an American multireligious heritage. In Finding Mecca in America: How Islam is Becoming an American Religion, Muchit Bilici explores the rapid increase of American Muslim educational, cultural, religious, and civic institutions, as well as how September 11, the so-called war on terror, and most recently media coverage of the Arab Spring have given American Muslims a unique visibility in the American public sphere. Bilici demonstrates how multifarious individuals and coalitions have banded together to counter negative public sentiments toward Islam and Muslims, to advocate for legal protections against discrimination, and to help fashion a cultural and religious niche for the community’s faith, practices, and presence. Even as public narratives about Muslims tend to emphasize “elements of chaos, instability, and danger,” sympathetic representations of American Muslims as “next-door neighbors” or “decent Americans struggling for their civil rights and in need of empathy, understanding and respect” are becoming more prevalent in major media venues from National Public Radio to the New York Times (p. 3). In turn, Muslims are demonstrating their collective abilities to define authentically American identities through social and political activism, forms of strategic public outreach, even ethnic comedy ...